An assessment of postcranial indices, ratios, and body mass versus eco‐geographical variables of prehistoric Jomon, Yayoi agriculturalists, and Kumejima Islanders of Japan. Issue 5 (10th May 2017) - Seguchi, Noriko; Quintyn, Conrad B.; Yonemoto, Shiori; Takamuku, Hirofumi
Abstract: Objectives: We explore variations in body and limb proportions of the Jomon hunter‐gatherers (14, 000–2500 BP), the Yayoi agriculturalists (2500–1700 BP) of Japan, and the Kumejima Islanders of the Ryukyus (1600–1800 AD) with 11 geographically diverse skeletal postcranial samples from Africa, Europe, Asia, Australia, and North America using brachial‐crural indices, femur head‐breadth‐to‐femur length ratio, femur head‐breadth‐to‐lower‐limb‐length ratio, and body mass as indicators of phenotypic climatic adaptation. Specifically, we test the hypothesis that variation in limb proportions seen in Jomon, Yayoi, and Kumejima is a complex interaction of genetic adaptation; development and allometric constraints; selection, gene flow and genetic drift with changing cultural factors (i.e., nutrition) and climate. METHODS: The skeletal data (1127 individuals) were subjected to principle components analysis, Manly's permutation multiple regression tests, and Relethford‐Blangero analysis. RESULTS: The results of Manly's tests indicate that body proportions and body mass are significantly correlated with latitude, and minimum and maximum temperatures while limb proportions were not significantly correlated with these climatic variables. Principal components plots separated "climatic zones:" tropical, temperate, and arctic populations. The indigenous Jomon showed cold‐adapted body proportions and warm‐adapted limb proportions. Kumejima showed cold‐adapted body proportions and limbs. The Yayoi adhered to the Allen‐Bergmann expectation of cold‐adapted body and limb proportions. Relethford‐Blangero analysis showed that Kumejima experienced gene flow indicated by high observed variances while Jomon experienced genetic drift indicated by low observed variances. CONCLUSIONS: The complex interaction of evolutionary forces and development/nutritional constraints are implicated in the mismatch of limb and body proportions.